Palatal Abscess in a Pediatric Patient: Report of a Case - Sumer, A. Pina; Celenk, Peruze (European Journal of Dentistry, 2008)
The palatal mass can pose a difficult diagnostic dilemma for the clinician. In differential diagnosis of the palatal mass, dental causes must be considered because they are so common. The palatal abscess typically represents the palatally directed drainage of an infection of pulpal or periodontal origin. The palatal abscess is often observed in the premolar-molar region and presents as a compressible mass or swelling usually lateral to the midline. This study reports the unusual case of a 5-year-old girl with a palatal abscess adjacent to the midline. (Eur J Dent 2008;2:291-293)
Keywords: Palatal abscess; Odontogenic infections; Treatment